IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM pada SEKOLAH INKLUSI di SD MUTIARA BUNDA - Kharimah, Alma Nur; Sumarna, Elan; Parhan, Muhamad (Al-Ulum: Jurnal Pendidikan Islam, 2024)
Statistical data from the coordinating ministry for human and cultural development in 2021 explains that as many as 2,197,833 children aged 5-19 years are people with disabilities, this is a challenge for Indonesia in the development and distribution of education throughout society. One aspect that can overcome this problem is an inclusive education system in every school with Islamic religious education being an integral part of this education system. Islamic religious education has an important role in developing the attitudes, values, morals, religious and social morals of children with disabilities in society. Therefore, this article will discuss the implementation of Islamic religious education learning at inclusive schools at Mutiara Bunda Elementary School. This research aims to analyze and provide information regarding the implementation of inclusive Islamic Religious Education which is already running well at Mutiara Bunda Elementary School. This research uses a qualitative approach with a descriptive method. Data collection was carried out through observation of the PAI learning process, joint interviews with key informants consisting of school principals, Special Education Special Services (PKLK) coordinators, and PAI teachers and relevant literature studies. The conclusion of this article is that things that support the implementation of inclusive education in Islamic religious education are good school management and school communication with all related parties.